Active phytochemicals present in the Guava Tree (Psidium Guajava) leaf Extracts that grow in Uganda. - David Serunjogi (Student's Journal of Health Research, 2020)
Background:   The Guava tree is small in the myrtle family (Myrtaceae), native to Mexico, Central America, the Caribbean, and northern South America. It contains a high content of organic and inorganic compounds like secondary metabolites such as antioxidants, polyphenols, antiviral compounds, and anti-inflammatory compounds. Such chemicals are produced by plants through primary or secondary metabolism whereas Guava products have been used as a source of medicine and while they have proved to work effectively, little is known about the composition of such plant origin products from Uganda.   Methodology:    The maceration method of extraction was used to obtain the guava extract. The leaves were crushed into a powder using a blender and 20g of the powder was added into differently labeled beakers containing 100mls of distilled water and 100mls of increasing concentration of methanol from 30%, 50%, and 70%. The analysis involved Saponins, Phenols and Tannins, Terpenoids, Flavonoids, and Glycosides, and Laboratory tests are done included the Ferric Chloride test, Shinoda test, Salkowski test, Concentrate H2SO4 test, and Foam test.   Results and discussion:    Phytochemicals (Saponins, Phenols and Tannins, Terpenoids, Flavonoids, and Glycosides) are present in the leaves of the guava tree (Psidium guajava) that grows in Uganda. Psidium guajava extract obtained using distilled water contained all the phytochemicals tested apart from terpenoids which showed a negative test result. Methanol of increasing concentrations can also be used to extract phytochemicals from the leaves.   Conclusions and recommendations:    It's now evident that the Guava tree that grows in Uganda contains phytochemicals (secondary metabolites). Water and methanol of 30%, 50%, and 70% can be used for extraction. Future detailed studies in Africa should focus on the purification of these active secondary metabolites and also determine their concentration. Other parts of the plant such as its bark, roots, and fruits need to be studied.